Analisis Teknologi Smartphone dalam Mendukung Kegiatan Akademis di Universitas Hamzanwadi Menggunakan Technology Acceptance Model - Muhammad Zamroni Uska; Rasyid Hardi Wirasasmita (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The use of smartphones has been widely used by the public, especially among students. The less effective use of smartphones in supporting academic activities on campus, it is necessary to analyze the acceptance of smartphone users using the Technology Acceptance Model (TAM). The purpose of this study is to: 1) find out the effect of perceived usefulness and perceived ease of use on attitude toward using, 2) find out the effect of perceived usefulness, perceived ease of use, and attitude toward using against actual technology use. The type of this study is a quantitative analysis with a survey method conducted at Hamzanwadi niversity with a population of 3,549 people and a total sample of 97 people using cluster sampling as a method used for sampling. The data collection is a questionnaire with a Likert scale. The data analysis used descriptive analysis and SEM. The results of this study show that there is a perceived usefulness influencethe influence of perceived usefulness and perceived ease of use on attitude toward using (Ï0.05), and the effect of perceived usefulness, perceived ease of use, and attitude toward using on actual technology use (Ï 0.05) in using smartphone technology as a media supporting academic activities.